Mastitis di Jawa Barat, Indonesia: Etiologi dan Opsi Pencegahan - Sarasati Windria (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
Mastitis is Mastitis is an inflammation of the udder. Mastitis is mainly caused by pathogenic bacteria both bacterial and yeast. The purpose of this review is to describe the ecology and epidemiology of mastitis prevalent in West Java and to propose control options that may be suitable for the West Java situation. The review was conducted using published papers about mastitis in West Java and government documentation. We determined that the major classification mastitis in West Java are clinical mastitis and subclinical mastitis. We also determined that the major pathogens agent of mastitis both clinical and subclinical mastitis are bacteriology and mycology agent. Education of farmers is an important part of any control program. The ecology and epidemiology of mastitis in West Java are still largely not understood. Future studies should be aimed at the evaluation of the proposed methods of disease control, an understanding of the impact of mastitis infection on dairy production in West Java and the role of the movement of dairy cattle products into and among regions in West Java.